2019
DOI: 10.3390/w11102193
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphodynamics in Argan Woodlands, South Morocco

Abstract: The endemic argan tree (Argania spinosa) populations in South Morocco are highly degraded due to their use as a biomass resource in dry years and illegal firewood extraction. The intensification and expansion of agricultural land lead to a retreat of the wooded area, while the remaining argan open woodlands are often overgrazed. Thus, canopy-covered areas decrease while areas without vegetation cover between the argan trees increase. In total, 36 rainfall simulation experiments as well as 60 infiltration measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 77 publications
(119 reference statements)
1
27
0
Order By: Relevance
“…During summer and autumn, it may even act as a protection for underlying mineral sediments. Kirchhoff et al (2019a) found that tree-covered areas in argan woodlands show higher values of soil organic matter and lower erodibility compared with inter-tree areas. Our results support this general distinction insofar as soil surface properties and emission fluxes vary only slightly compared with all other surface types.…”
Section: Rh2mentioning
confidence: 93%
See 3 more Smart Citations
“…During summer and autumn, it may even act as a protection for underlying mineral sediments. Kirchhoff et al (2019a) found that tree-covered areas in argan woodlands show higher values of soil organic matter and lower erodibility compared with inter-tree areas. Our results support this general distinction insofar as soil surface properties and emission fluxes vary only slightly compared with all other surface types.…”
Section: Rh2mentioning
confidence: 93%
“…The 100m × 100m test site IRG1c is part of a larger research area situated on an alluvial fan, formed by Wadi Irguitène originating from the High Atlas in the north (Kirchhoff et al, 2019a;Kirchhoff et al, 2019b). It belongs to the remaining natural habitat of the argan tree Argania spinosa, which can be assumed to be a paramount keystone species in this environment.…”
Section: Location and Test Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Kirchhoff et al [15] presented exotic research carried out in a poorly-studied region of Northern Africa, where the endemic argan tree (Argania Spinosa) populations are highly degraded due to their use as a biomass resource in dry years and illegal firewood extraction. In total, 36 rainfall simulation experiments, as well as 60 infiltration measurements, were conducted to investigate the potential difference between tree-covered areas and bare inter-tree spaces.…”
Section: Summary Of This Special Issuementioning
confidence: 99%